Hydrological Drought Assessment and Analysis of its Characteristic Using the Stream flow Drought Index (SDI) at Hydrometry Stations in the Province of Ardabil - Hamed Amini; Abazar Esmali Ouri; Raoof Mostafazadeh; Mearaj Sharari; Mohsen Zabihi (پژوهش‌های آبخیزداری, 2019)
Hydrological drought can lead to a decrease in river flow and loss of the river ecosystem quality, which limits human use of the surface water. The stream flow drought index (SDI) has been used to assess the hydrological droughts in 33 hydrometric stations of the Province of Ardabil. The SDI was calculated using the DrinC software; subsequently, characteristics of the hydrological drought were classified and analyzed. The inter-relationship of the different components of hydrological drought with those of the flow rate were also examined. Subsequently, some of the hydrological drought characteristics were interpolated to detect the spatial variations. The results indicated that all of the studied stations experienced drought events. The maximum dry-period was 62 months at the Samian Station. The results of the standard classification of the SDI in 14 stations (Aladizge, Pole-Almas, Anbaran, Baroogh, Boran, Dostbeyglu, Gilandeh, Iril, Koozetopraghi, Mashiran, Neour, Samian, Shamsabad and Sola) indicated that the number of wet-months were larger than that of the dry-months. The severest drought was observed at the Pole-Almas Station (-1.05), while the highest frequency of wet-months had been recorded at the same station. The average intensity of the highest and lowest hydrological drought events at the Pole-Almas and Anbaran Stations were -1.05 and -0.57, respectively. The spatial variations of drought occurrence showed that the stations located in the upstream areas and the Sabalan piedmonts had the lowest drought occurrence in the study area. The severe and severest drought events had been occurred in small rivers with low discharge.